Executive functions in volleyball- and badminton players - Schmitz, G.; Effenberg, A.O. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Motor control and cognitive executive control are interrelated, but the underlying mechanisms are largely unknown. 10 weeks of table tennis training can improve executive control in children with developmental coordination disorder (Tsai, 2009). A similar effect was reported for healthy adults after two years of baseball- but not tennis-training, suggesting that cognitive improvements are based on sport-specific demands (Kida et al., 2005). The aim of the present study was to investigate (1.) whether experts from different sports have different executive abilities and (2.) if sport-specific training has acute effects on executive functions. Methods: 47 athletes participated in the study (aged 24.9 ±5.2 years, 18 female). 19 were volleyball-players (expertise: 14.8 ±2.8 years) and 8 Badminton-Players (expertise: 13.8 ±8.3 years). 20 subjects from various sports (expertise: 8.0 ±5.7 years) served as control-group. Executive functions were assessed with Tower of London (ToL), Stroop-Test (ST), Trail Making Test (TMT), FAIR II Test (FT) and a Maze Test (MT), latter including a reference trail (rMT) as screening tool for visuomotor control. All tests were applied before and in a modified version 50 minutes after sport-specific training or social activity (control-group). Results were submitted to repeated measure ANOVAs and significant effects were decomposed with Fisher´s LSD test. For clarity only p-levels are reported here. Results: (1.) Volleyball-players performed better in rMT than badminton-players and the control-group (both p<0.01). Badminton-players were better than the other groups in MT (both p<0.05) and better than volleyball-players in ToL (p<0.05). Expertise correlated negatively with performance in TMT across all subjects (r=-0.44, p<0.01). (2.) All groups significantly enhanced their performance from pre- to post-test in FT (p<0.001), MT (p<0.001), TMT (p<0.05), ST (p<0.001) and ToL (p<0.05) but not in rMT (p>0.05). Rates of enhancement did not differ significantly between groups (p>0.05). Discussion: (1.) Results confirm that executive and probably sensorimotor abilities differ between experts of various disciplines. Higher performance of badminton-players in MT and ToL might be based on more effective planning and decision-making, since those functions are addresses by both tests. The negative correlation of TMT and expertise might indicate a detrimental effect of long-term sport-specific training on cognitive flexibility. (2.) Enhancements from pre- to post-test can be explained by repeated measures effects. Therefore no acute effect of sport-sprecific training was found.